The Mobi-C cervical disc for one-level and two-level cervical disc replacement: a review of the literature - Alvin MD (Dove Medical Press, 2014)
Matthew D Alvin,1,2 Thomas E Mroz1,3,41Cleveland Clinic Center for Spine Health, Cleveland Clinic, Cleveland, OH, USA; 2Case Western Reserve University School of Medicine, Cleveland, OH, USA; 3Cleveland Clinic Lerner College of Medicine, Cleveland, OH, USA; 4Department of Neurological Surgery, Cleveland Clinic, Cleveland, OH, USABackground: Cervical disc arthroplasty (CDA) is a novel motion-preserving procedure that is an alternative to fusion. The Mobi-C disc prosthesis, one of many Food and Drug Administration (FDA)-approved devices for CDA, is the only FDA-approved prosthesis for two-level CDA. Hence, it may allow for improved outcomes compared with multilevel fusion procedures.Purpose: To critically assess the available literature on CDA with the Mobi-C prosthesis, with a focus on two-level CDA.Methods: All clinical articles involving the Mobi-C disc prosthesis for CDA through September 1, 2014 were identified on Medline. Any paper that presented Mobi-C CDA clinical results was included. Study design, sample size, length of follow-up, use of statistical analysis, quality of life outcome scores, conflict of interest, and complications were recorded.Results: Fifteen studies were included that investigated Mobi-C CDA, only one of which was a level Ib randomized control trial. All studies included showed non-inferiority of one-level Mobi-C CDA to one-level anterior cervical discectomy and fusion (ACDF). Only one study analyzed outcomes of one-level versus two-level Mobi-C CDA, and only one study analyzed two-level Mobi-C CDA versus two-level ACDF. In comparison with other cervical disc prostheses, the Mobi-C prosthesis is associated with higher rates of heterotopic ossification (HO). Studies with conflicts of interest reported lower rates of HO. Adjacent segment degeneration or disease, along with other complications, were not assessed in most studies.Conclusion: One-level Mobi-C CDA is non-inferior, but not superior, to one-level ACDF for patients with cervical degenerative disc disease. The Mobi-C CDA procedure is associated with high rates of HO. Two-level Mobi-C CDA may be superior to two-level ACDF. However, insufficient evidence exists, thereby mandating a need for unbiased, well-designed prospective studies with well-defined outcomes in the future.Keywords: Mobi-C, cervical disc arthroplasty, total disc replacement, ACDF, quality of life, outcomes, effectiveness, cervical spine